Sposoby wskazywania osób w rękopisie ZNiO sygn. 7529/III - Wojciechowska, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 2010)
The article presents linguistic habits in range of person indication that have been preserved in the protocols of the Society of Friends of Fine Arts in Lvov (1886–1894). The analysis of the text proves that a nomination has been subject to linguistic etiquette rigour. In reconstructed naming model dominates communal (justified by membership) and non-communal titular (used in order to express esteem and to emphasis social rank of indicated person). The naming material illustrates a strong sense of belonging to the elite and simultaneously presents the hierarchy inside the community. The main factors that determine the means of person indication in protocols are: the formality of communicational situation, the genre requirements, the rank of indicated person, the social position and the competence of a recording clerk.